1999
DOI: 10.1103/physrevd.60.033006
|View full text |Cite
|
Sign up to set email alerts
|

Possible effects of quantum mechanics violation induced by certain quantum-gravity effects on neutrino oscillations

Abstract: In this work we tried extensively to apply the EHNS postulation about the quantum mechanics violation effects induced by the quantum gravity of black holes to neutrino oscillations. The possibilities for observing such effects in the neutrino experiments (in progress and/or accessible in the near future) were discussed. Of them, an interesting one was outlined specially.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Quantum gravity effects in neutrino systems have been investigated with increasing attention in the last decade, as a result of the evidence for neutrino flavor oscillations. Early attempts tried to interpret the solar neutrino puzzle [8,9,10] or the atmospheric ν anomaly [10] in terms of decoherence. After the first convincing evidence for atmospheric neutrino oscillations [15], a quantitative analysis was performed in [11], considering possible decoherence effects in the ν µ → ν µ channel (see also [12]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantum gravity effects in neutrino systems have been investigated with increasing attention in the last decade, as a result of the evidence for neutrino flavor oscillations. Early attempts tried to interpret the solar neutrino puzzle [8,9,10] or the atmospheric ν anomaly [10] in terms of decoherence. After the first convincing evidence for atmospheric neutrino oscillations [15], a quantitative analysis was performed in [11], considering possible decoherence effects in the ν µ → ν µ channel (see also [12]).…”
Section: Introductionmentioning
confidence: 99%
“…However, lacking an "ab initio" theory of quantum gravity decoherence, its effects can only be parameterized in a model-dependent (and somewhat arbitrary) way. Searches with neutral kaon oscillations [3,4,5,6], neutron interferometry [3,7] and, more recently, neutrino oscillations [8,9,10,11,12,13,14], have found no evidence for such effects so far, and have placed bounds on model parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrinos travelling over very long baselines, such as from supernovae would be expected to experience this phenomenon. New physics beyond the Standard Model is required for this effect to be observable over small distances, such as quantum gravity in the context of black hole thermodynamics [14].…”
Section: Neutrino Decoherencementioning
confidence: 99%
“…Gravitational induced neutrino-antineutrino oscillations have also been investigated [25,26]. Quantum gravity effects and the possible violation of the equivalence principle are studied in [27][28][29][30][31]. In previous work [32], neutrino lensing in the Schwarzschild geometry under the weak gravity limit has been studied where it was shown that, unlike in the flat spacetime neutrino, neutrino flavor transition probability in the weak gravity neutrino lensing contains the information about the absolute neutrino mass and their hierarchy.…”
Section: Introductionmentioning
confidence: 99%